Women’s empowerment in rural Ethiopia - Mulema, Annet A.; Nigussie, L. (Oxford University Press, 2019)
The Women’s Empowerment in Agriculture Index (WEAI) is the first standardized tool to measure empowerment in the agricultural sector. Most of the work on measuring women’s empowerment has so far focused on developing quantitative measures to the exclusion of qualitative measures that could add more to our understanding of the local meaning of empowerment and how it can be measured. Domains and indicators of empowerment that are associated with the local contextual meaning can help better identify best practices that unleash the full potential of women to effectively increase production, income, and food and nutritional security. The chapter conducts a systematic review of policy documents, reports from national surveys, and publications from projects whose goal is to empower women, to determine the indicators measured, aided by the WEAI. Using one case study in Ethiopia, the chapter examines women’s empowerment domains and indicators at three levels—policy, community, and household.